1996
DOI: 10.1097/00000421-199610000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of CA 15-3, Mucin-like Carcinoma-Associated Antigen, Tumor Polypeptide Antigen, and Carcinoembryonic Antigen in Monitoring Early Breast Cancer Patients

Abstract: A total of 209 postsurgical breast cancer patients were prospectively monitored with simultaneous serum level estimations of CA 15,3, mucin-like carcinoma-associated antigen (MCA), tumor polypeptide antigen (TPA), and carcinoembryonic antigen (CEA); 141 (67.5%) were free of recurrence and 68 (32.5%) developed metastases during the follow-up. The mean values of tested tumor markers differed significantly in those with progressive disease compared with those free of disease recurrence. The sensitivity of tumor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…With regard to CEA, TPA and CA15.3, CA15.3 (with MCA cut-off value ≥ 11 UI/mL) and TPA (with MCA cut-off value ≥ 15 UI/mL) were more sensitive than both remaining indicators. However, only with ≥ 11 U/mL MCA cut-off value, sensitivity increased slightly (from 53% to 58%) after the association of MCA with CA15.3, while as we [4,7,9-11] and others [22,26,33] previously reported, it occurred significantly when TPA was associated with CA15.3 and CEA (Tables 1, 2). In other studies a range of MCA sensitivity similar to CA15.3 and no significant increase in sensitivity when MCA was combined with CA15.3 were found [14,27,34,35].…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…With regard to CEA, TPA and CA15.3, CA15.3 (with MCA cut-off value ≥ 11 UI/mL) and TPA (with MCA cut-off value ≥ 15 UI/mL) were more sensitive than both remaining indicators. However, only with ≥ 11 U/mL MCA cut-off value, sensitivity increased slightly (from 53% to 58%) after the association of MCA with CA15.3, while as we [4,7,9-11] and others [22,26,33] previously reported, it occurred significantly when TPA was associated with CA15.3 and CEA (Tables 1, 2). In other studies a range of MCA sensitivity similar to CA15.3 and no significant increase in sensitivity when MCA was combined with CA15.3 were found [14,27,34,35].…”
Section: Discussionmentioning
confidence: 53%
“…However, different cut-off values have been reported for MCA [17,20]. Besides conflicting data have been found both as to MCA sensitivity and specificity compared to CA15.3 [22-25] and the MCA-CA15.3 usefulness [14,15,22,26,27]. Finally, as far as we know, no previous study compared MCA-CA15.3 to CEA-TPA-CA15.3 association.…”
Section: Introductionmentioning
confidence: 99%
“…CA 15‐3 is elevated in the serum/plasma of ∼ 75% of women with metastasized breast cancer; however, these levels can also be raised due to the presence of other conditions or cancers. Pectasides and coworkers found that patients with postsurgical breast cancer prospectively monitored with simultaneous serum level estimations for CA 15‐3 and CEA, resulted in sensitivity values of 68.2 and 34.1% respectively 45. The markers most often elevated in advanced CRC are CEA and CA 19‐9, but neither of these is useful as a screening test for CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we compared the gene expression data with the detected Ca15-3 serum levels. Increased serum levels of the tumour marker Ca 15-3 have been associated with advanced disease and poor outcome in several studies [14,15]. …”
Section: Introductionmentioning
confidence: 99%